An Integrated Approach to Innovation: the Way of the EU and Poland - Anna Lewandowska (Barometr Regionalny)
Supporting innovation, particularly technological progress, is considered a substantial element of policies towards sustainable development. It is considered that both research and innovation contribute to employment growth, increase prosperity and quality of life. Given the above assumptions and the role of research in the knowledge-based economy, the European Union has decided to create their own innovative policies and instruments of implementation. The paper defines the areas of convergence between cohesion policy and innovation policy implemented by the EU and Polish policy implemented at national and regional level. In Poland, innovation, competitiveness and eco-efficiency play a significant role in the regional disparities and an integrated approach to innovation can provide benefits for both Poland and the EU.